Aplikasi Web Untuk Klasifikasi Stunting Pada Balita Dengan Menggunakan Metode K-Nearest Neighbours (Studi Kasus Posyandu Jawu Kidul) - Sholikhin, Nur Ali; Atmojo, Suryo (Faculty of Engineering, Wijaya Putra University, 2022)
Stunting is a state of inability to develop in children under five years old due to abnormalities in newborn children. Health issues are still a public issue in Indonesia, especially the age group that is often affected by nutritional issues is childhood. Children who experience the adverse effects of health problems early on experience developmental delays, illness, and even death. The nutritional status of the K-Nearest Neighbor technique is the condition of the body due to examples of food intake and use of supplements. Assessment of the health status of newborns is useful for knowing the health status of infants based on BB/U (weight for age), TB/U (age level), BB/TB (weight for age). The framework planned is a framework for determining stunting status in infants using the KNN technique. Classification aims to determine nutritional status, height status, weight status of children under five and stunting status. Determination of stunting status in toddlers, aims to support, accelerate and facilitate the process of handling stunting cases at the Posyandu in Jawu Kidul Village.